(untitled) (Punyawati Journal, 2026)
This study examines how farmers in Lele Valley, Godawari Municipality, Lalitpur, Nepal, use social media to access agricultural information and government subsidy programs. Despite increasing digital adoption in rural Nepal, there is limited evidence on how farmers integrate social media with traditional information sources and how socio-demographic factors affect adoption. A quantitative research design employing descriptive and causal-comparative methods was applied, using structured surveys administered to 112 commercial farmers who rely on social media for their farming activities. Findings reveal that traditional sources such as radio (82.1%) and newspapers (70.5%) remain dominant, while digital platforms like YouTube (69.6%) and Facebook (66.1%) are gaining traction. Access to subsidies is uneven, with 62.5% of respondents receiving institutional support and 30% receiving none. Socio-demographic characteristics including gender, location, and farming experience significantly influence income, digital adoption, and participation in support programs. The study concludes that social media can enhance agricultural communication and facilitate subsidy access, but adoption is limited by connectivity issues, digital literacy gaps, and institutional barriers. Policy recommendations include strengthening digital literacy programs, streamlining subsidy procedures, integrating social media into extension services, and supporting farmer-led digital networks for knowledge sharing and equitable access.